Neuromuscular junctions are stable in patients with cancer cachexia - Boehm, Ines (J Clin Invest, 2020)
Cancer cachexia is a major cause of patient morbidity and mortality, with no efficacious treatment or management strategy. Despite cachexia sharing pathophysiological features with a number of neuromuscular wasting conditions, including age-related sarcopenia, the mechanisms underlying cachexia remain poorly understood. Studies of related conditions suggest that pathological targeting of the neuromuscular junction (NMJ) may play a key role in cachexia, but this has yet to be investigated in human patients. Here, high-resolution morphological analyses were undertaken on NMJs of rectus abdominis obtained from patients undergoing upper GI cancer surgery compared with controls (N = 30; n = 1,165 NMJs). Cancer patients included those with cachexia and weight-stable disease. Despite the low skeletal muscle index and significant muscle fiber atrophy (P < 0.0001) in patients with cachexia, NMJ morphology was fully conserved. No significant differences were observed in any of the pre- and postsynaptic variables measured. We conclude that NMJs remain structurally intact in rectus abdominis in both cancer and cachexia, suggesting that denervation of skeletal muscle is not a major driver of pathogenesis. The absence of NMJ pathology is in stark contrast to what is found in related conditions, such as age-related sarcopenia, and supports the hypothesis that intrinsic changes within skeletal muscle, independent of any changes in motor neurons, represent the primary locus of neuromuscular pathology in cancer cachexia.